Importance Use of Indonesian in Higher Education: Bahasa Indonesia - Arif Saputra, Andika; Rafsanjani, Ali Hasan; Rizky Fadhilah, Fawwaz; Miftahus Saadah , Muhammad; Repelita, Tridays (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
The use of Indonesian in higher education has a very important role in maintaining national identity and promoting a deeper understanding of local culture. In an academic context, Indonesian is not only a communication tool, but also a teaching and research medium that can improve the quality of education. The use of this national language helps strengthen a sense of togetherness among students from various regions, reduces communication barriers, and facilitates effective knowledge transfer. Apart from that, good command of Indonesian among students and lecturers can support the government's efforts to preserve and develop the national language. This research highlights various aspects that show the importance of using Indonesian in higher education, including its impact on students' intellectual development, social integration, and cultural preservation.